Gel electrolyte, preparation method of gel electrolyte and zinc-air battery

By using specially made gel electrolytes in zinc-air batteries, the problem of dendrite and hydrogen evolution reaction is solved, the stability and cycle life of the battery are significantly improved, and the mechanical strength and chemical stability of the gel electrolyte are enhanced.

CN119912637AActive Publication Date: 2025-05-02VIT NEW ENERGY (GUANGDONG) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510202499.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-05-02
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

There is dendrite phenomenon and hydrogen evolution reaction in zinc-air batteries, which affects the battery performance and life.

Method used

A gel electrolyte is employed, which consists of a water-soluble monomer, water, an electrolyte salt, a first electrolyte additive (dipropylene glycol and zinc trifluoromethylsulfonate), a crosslinker and an initiator, and a gel electrolyte layer is formed by a specific preparation method.

Benefits of technology

Effectively inhibit the growth of dendrites, reduce hydrogen evolution reaction, improve the stability and cycle life of zinc-air batteries, and enhance the mechanical strength and chemical stability of gel electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912637A_ABST
    Figure CN119912637A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of zinc-air batteries, and discloses a gel electrolyte, a preparation method of the gel electrolyte and a zinc-air battery, the gel electrolyte comprises the following components: a water-soluble monomer, water, an electrolyte salt, a first electrolyte additive, a cross-linking agent and an initiator; the first electrolyte additive comprises dipropylene glycol and zinc trifluoromethanesulfonate. By optimizing the composition and the preparation method of the gel electrolyte, the key technical problems in the zinc-air battery are effectively solved, the performance of the battery is improved, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zinc-air batteries, and in particular to a gel electrolyte, a preparation method of the gel electrolyte and a zinc-air battery. Background Art

[0002] With the continuous growth of global energy demand and the serious environmental problems and energy crisis caused by fossil energy, it is imperative to develop efficient, environmentally friendly and sustainable new energy technologies. In this context, zinc-air batteries have attracted extensive attention from the scientific research and industry circles due to their high energy density, high safety performance, environmental protection characteristics and relatively low cost.

[0003] Quasi-solid-state zinc-air battery mainly consists of three parts: air positive electrode, zinc negative electrode and gel electrolyte. In an alkaline environment, the working principle of the battery is based on a series of electrochemical reactions. During the discharge process, metal zinc (Zn) acts as the negative electrode, loses electrons and is oxidized into zinc ions (Zn²⁺); at the same time, oxygen (O2) in the air diffuses to the air positive electrode, where it undergoes an oxygen reduction reaction (ORR) to generate hydroxide ions (OH⁻), and during the charging process, the air positive electrode undergoes an oxygen evolution reaction (OER), that is, the hydroxide ions lose electrons and release oxygen.

[0004] Among them, the existing technology of zinc-air batteries still has some problems that need to be solved. One of the primary problems is the dendrite phenomenon. Due to the unevenness of the initial substrate surface of the zinc negative electrode, the electric field strength increases at locations with higher curvature, and the activity of these sites is relatively high. Therefore, zincate is preferentially reduced at these sites with lower energy barriers and attracts more zincate to accumulate. As the charge and discharge cycle proceeds, this accumulation effect gradually intensifies, eventually forming dendrites, which seriously affects the performance and life of the battery.

[0005] Another important issue is the hydrogen evolution reaction. On the surface of the zinc negative electrode, in addition to the main zinc oxidation reaction, other competing electrochemical reactions may occur. Among them, the hydrogen evolution reaction is a side reaction that cannot be ignored. When the hydrogen ions in the electrolyte solution obtain enough electrons, they combine to produce hydrogen gas. This reaction is particularly significant in zinc-air batteries because it competes with the zinc oxidation reaction for the same electrons. The hydrogen evolution reaction not only reduces the coulombic efficiency of the battery, but may also cause damage to the structure and performance of the battery.

[0006] In summary, although quasi-solid-state zinc-air batteries have broad application prospects, the dendrite problem and hydrogen evolution problem are still the key factors restricting their further development and application. Therefore, the technical innovation and solution research for these problems have important practical significance and scientific research value. Summary of the invention

[0007] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a gel electrolyte and a preparation method and application thereof.

[0008] The objective of the present invention is achieved through the following technical solutions: A gel electrolyte comprises the following components: a water-soluble monomer, water, an electrolyte salt, a first electrolyte additive, a crosslinking agent and a thermal initiator; The first electrolyte additive includes dipropylene glycol and zinc trifluoromethanesulfonate.

[0009] Furthermore, the mass ratio of the dipropylene glycol, zinc trifluoromethanesulfonate and water is (1-3): (6-8):10.

[0010] Furthermore, the gel electrolyte also includes a second electrolyte additive, and the second electrolyte additive includes zinc acetate.

[0011] Furthermore, the water-soluble monomer is an acrylamide monomer.

[0012] Furthermore, the electrolyte salt is at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide and the like.

[0013] Furthermore, the cross-linking agent is at least one of methylenebisacrylamide, N-hydroxymethylacrylamide, acrylamide-PEG-hydroxyl, and the like.

[0014] Furthermore, the initiator is at least one of potassium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisoheptylnitrile and the like.

[0015] Furthermore, the gel electrolyte also includes a third electrolyte additive, and the third electrolyte additive is modified porous zinc oxide nanorods.

[0016] The present invention also provides a method for preparing the above-mentioned gel electrolyte, comprising the following steps: S1: adding the first electrolyte additive to the water in proportion, and performing a first stirring to obtain a first mixed solution; S2: adding the water-soluble monomer to the first mixed solution in proportion, stirring for a second time, continuing to add the crosslinking agent and the initiator, stirring for a third time, and obtaining a gel precursor solution; S3: injecting the gel precursor solution into the template, drying it under certain conditions, and then immersing the template containing the gel into an electrolyte salt solution, soaking it, and then taking the gel out of the template to obtain a gel electrolyte.

[0017] Furthermore, in step S2, the mass concentration of the water-soluble monomer in the mixed solution is 0.25 g / mL to 0.3 g / mL.

[0018] Furthermore, in step S2, the third stirring is to stir the cross-linking agent and the initiator until they are fully dissolved.

[0019] Furthermore, the drying conditions in step S3 are: drying at 40° C. to 85° C. for 4 h to 12 h.

[0020] Furthermore, the molar concentration of the electrolyte salt solution is 2 mol / L to 8 mol / L.

[0021] Furthermore, zinc acetate is added during the preparation of the electrolyte salt solution in step S3, and the molar concentration of zinc acetate in the electrolyte salt solution is 0.1 mol / L~0.5 mol / L. Among them, zinc acetate is a weak acid and strong base salt, which can be hydrolyzed in an aqueous solution to produce hydroxide ions (OH⁻), which helps to maintain the alkaline environment of the gel electrolyte during the immersion process. Furthermore, zinc acetate can affect the deposition behavior on the surface of the zinc negative electrode, help to form a more uniform zinc deposition layer, thereby reducing the formation of dendrites. At the same time, the zinc deposition layer can reduce the direct contact between the zinc negative electrode and the electrolyte, thereby reducing the occurrence of hydrogen evolution reaction.

[0022] Furthermore, in step S1, the first electrolyte additive and the third electrolyte additive are added to the water in proportion, and stirred for the first time to obtain a first mixed solution.

[0023] Furthermore, the third electrolyte additive is modified porous zinc oxide nanorods, and the mass ratio of the modified porous zinc oxide nanorods to water is (0.05-0.2):10.

[0024] Furthermore, the modified porous zinc oxide nanorods are prepared by the following steps: The zinc acetate ethanol solution and the oxalic acid dihydrate ethanol solution are mixed uniformly in a certain proportion to obtain a second mixed solution; placing the second mixed solution in a reaction kettle, reacting at 70-90° C. for 4-6 hours to obtain a reaction product, washing the reaction product with water or ethanol until it is neutral, and then drying the reaction product; The dried reaction product is annealed at 400-500° C. for 100-180 minutes to obtain porous zinc oxide nanorods; The porous zinc oxide nanorods are dispersed in a PEG-2000 solvent, and then filtered and dried after ultrasonic treatment to obtain modified porous zinc oxide nanorods.

[0025] Furthermore, the gel electrolyte is a gel electrolyte layer, and the thickness of the gel electrolyte layer is 1-5 mm.

[0026] The gel electrolyte prepared by the invention can be applied to zinc-air batteries to improve the electrochemical performance of the zinc-air batteries.

[0027] Compared with the prior art, the present invention has at least the following advantages: 1. The present invention adds a specific first electrolyte additive, namely, dipropylene glycol and zinc trifluoromethanesulfonate, to the gel electrolyte. Since dendrites are easily formed under an uneven electric field, the synergistic effect of dipropylene glycol and zinc trifluoromethanesulfonate can effectively adjust the electric field distribution on the surface of the zinc negative electrode, reduce the problem of increased electric field intensity caused by surface unevenness, thereby inhibiting the growth of dendrites, thereby improving the stability and cycle life of the zinc-air battery.

[0028] 2. The present invention uses dipropylene glycol as the first electrolyte additive, which not only has the function of improving electrolyte performance and inhibiting dendrite growth, but also can act as a plasticizer, which can enhance the elasticity and flexibility of the gel electrolyte, and help to improve the mechanical strength of the gel electrolyte, making it less likely to break, thereby enhancing the stability and durability of the gel electrolyte.

[0029] 3. Enhanced electrolyte stability: The present invention selects specific water-soluble monomers, electrolyte salts, first electrolyte additives, crosslinking agents and initiators. The synergistic effect of these components makes the gel electrolyte have excellent conductivity, mechanical strength and chemical stability. This helps to improve the working performance and long-term stability of the battery at high current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 : is the charge and discharge cycle curve of Example 1 of the present invention; Figure 2 This is the charge and discharge cycle curve of Example 3 of the present invention. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0032] Example 1 S1: adding dipropylene glycol and zinc trifluoromethanesulfonate into pure water (the mass ratio of dipropylene glycol, zinc trifluoromethanesulfonate and water is 2.5:7.5:10), stirring for the first time, and obtaining a first mixed solution; S2: adding 2.5 g of acrylamide to 10 ml of the first mixed solution, stirring for the second time, and then adding 2.5 mg of methylenebisacrylamide and 7.5 mg of potassium persulfate, stirring for the third time until fully dissolved, to obtain a gel precursor solution; S3: Inject the gel precursor solution into the template, dry it at 60°C for 12 hours, then immerse the template containing the gel in an electrolyte salt solution (the electrolyte salt solution is a mixed solution of 6M potassium hydroxide solution and 0.2M zinc acetate), soak it at room temperature for 48 hours, and then remove the gel from the template to obtain a gel electrolyte.

[0033] Example 2 S1: adding dipropylene glycol and zinc trifluoromethanesulfonate into pure water (the mass ratio of dipropylene glycol, zinc trifluoromethanesulfonate and water is 5:7.5:10), stirring for the first time, and obtaining a first mixed solution; The remaining steps S2 and S3 are the same as those in Example 1.

[0034] Example 3 S1: adding dipropylene glycol and zinc trifluoromethanesulfonate into pure water (the mass ratio of dipropylene glycol, zinc trifluoromethanesulfonate and water is 2.5:10:10), stirring for the first time, and obtaining a first mixed solution; The remaining steps S2 and S3 are the same as those in Example 1.

[0035] Example 4 S1: 0.5M zinc acetate ethanol solution and 0.5M oxalic acid dihydrate ethanol solution are mixed uniformly in an equal volume ratio to obtain a second mixed solution; the second mixed solution is placed in a reactor, reacted at 80°C for 5 hours to obtain a reaction product, the reaction product is washed with ethanol to neutrality, and then the reaction product is dried; the dried reaction product is annealed at 450°C for 150 minutes to obtain porous zinc oxide nanorods; the porous zinc oxide nanorods are dispersed in a PEG-2000 solvent, and filtered and dried after ultrasonic treatment to obtain modified porous zinc oxide nanorods; S2: adding dipropylene glycol, zinc trifluoromethanesulfonate, and modified porous zinc oxide nanorods into pure water (the mass ratio of dipropylene glycol, zinc trifluoromethanesulfonate, modified porous zinc oxide nanorods and water is 2.5:7.5:0.1:10), and stirring for the first time to obtain a first mixed solution; S3: adding 2.5 g of acrylamide to 10 ml of the first mixed solution, stirring for the second time, and then adding 2.5 mg of methylenebisacrylamide and 7.5 mg of potassium persulfate, stirring for the third time until fully dissolved, to obtain a gel precursor solution; S4: Inject the gel precursor solution into the template, dry it at 60°C for 12 hours, then immerse the template containing the gel in an electrolyte salt solution (the electrolyte salt solution is a mixed solution of 6M potassium hydroxide solution and 0.2M zinc acetate), soak it at room temperature for 48 hours, and then remove the gel from the template to obtain a gel electrolyte.

[0036] Comparative Example 1 S1: adding zinc trifluoromethanesulfonate to pure water (the mass ratio of zinc trifluoromethanesulfonate to water is 7.5:10), stirring for the first time, and obtaining a first mixed solution; The remaining steps S2 and S3 are the same as those in Example 1.

[0037] Comparative Example 2 S1: adding dipropylene glycol to pure water (the mass ratio of dipropylene glycol to water is 2.5:10), performing a first stirring to obtain a first mixed solution; The remaining steps S2 and S3 are the same as those in Example 1.

[0038] Comparative Example 3 S1: adding glycerol and zinc trifluoromethanesulfonate into pure water (the mass ratio of glycerol, zinc trifluoromethanesulfonate and water is 2.5:7.5:10), stirring for the first time, and obtaining a first mixed solution; The remaining steps S2 and S3 are the same as those in Example 1.

[0039] Comparative Example 4 S1: adding dipropylene glycol and zinc methanesulfonate into pure water (the mass ratio of dipropylene glycol, zinc trifluoromethanesulfonate and water is 2.5:7.5:10), stirring for the first time, and obtaining a first mixed solution; The remaining steps S2 and S3 are the same as those in Example 1.

[0040] Comparative Example 5 Commercially available zinc oxide nanoparticles (particle size <100 nm) were used to replace the modified porous zinc oxide nanorods, and the remaining steps were the same as those in Example 4.

[0041] Conductivity test: The gel electrolytes prepared in different embodiments and comparative examples were cut into the same size and then tested for conductivity using a conductivity meter. The specific results are shown in Table 1.

[0042] Cyclic test: The gel electrolytes prepared in different embodiments and comparative examples were cut into the same size (5 cm × 5 cm × 2 mm), and then assembled with the positive electrode (using commercial Pt / C catalyst) and the negative electrode (using zinc sheet) into a "sandwich" structure battery for cyclic test. The charge and discharge conditions were: charge for 1 h, discharge for 1 h, and the charge and discharge current was 5 mA / cm 2 , the specific test results are shown in Table 1.

[0043] Table 1 Test results of different embodiments and comparative examples Group Conductivity (S / cm) Cycle time (h) Example 1 0.685 160 Example 2 0.427 142 Example 3 0.401 128 Example 4 0.769 173 Comparative Example 1 0.389 84 Comparative Example 2 0.285 102 Comparative Example 3 The viscosity is too high to be completely removed Comparative Example 4 0.364 137 Comparative Example 5 0.484 146 Please refer to Table 1 and Figure 1 , Figure 2 The gel electrolyte of the present invention uses dipropylene glycol and zinc trifluoromethanesulfonate as the first electrolyte additive. It can be seen from the data of Examples 1 to 3 that after the prepared gel electrolyte is applied to the zinc-air battery, the cycle time of the zinc-air battery can be stably maintained at more than 120 hours. At the same time, Example 1 is a preferred embodiment. During the preparation process, the mass ratio of dipropylene glycol, zinc trifluoromethanesulfonate and water is controlled within the range of (1-3): (6-8): 10, so the conductivity of the prepared gel electrolyte can reach more than 0.6 S / cm, and the cycle time can reach more than 160 hours. In Examples 2 and 3, the amount of dipropylene glycol and zinc trifluoromethanesulfonate exceeds the optimal ratio range, resulting in a slight decrease in the test data. It can be seen that dipropylene glycol and zinc trifluoromethanesulfonate can significantly improve the electrochemical performance of zinc-air batteries after the component ratio is optimized.

[0044] Among them, Example 4 is that modified porous zinc oxide nanorods are added during the gel preparation process. It can be seen from the data that the conductivity and cycle time are significantly improved after the modified porous zinc oxide nanorods are added. This may be because the modified porous zinc oxide nanorods have a rich pore structure. These pores can be used as channels for ion transmission, promoting the rapid migration of ions in the gel electrolyte, thereby improving the ionic conductivity; at the same time, the modified porous zinc oxide nanorods can be embedded in the matrix of the gel electrolyte to form a stable network structure, thereby improving the overall mechanical strength and stability of the gel electrolyte.

[0045] The gel electrolyte in Comparative Example 1 does not contain dipropylene glycol, and the gel electrolyte in Comparative Example 2 does not contain zinc trifluoromethanesulfonate. It can be seen from the data that, compared with Example 1, the conductivity of the gel electrolytes in Comparative Example 1 and Comparative Example 2 is significantly reduced, while the cycle time is reduced by about 50%. It can be seen that the combined use of dipropylene glycol and zinc trifluoromethanesulfonate can significantly improve the electrochemical performance of the battery, and the use of any one of them alone cannot achieve the test results of Example 1.

[0046] In the preparation process of the gel electrolyte in Comparative Example 3, propylene glycol is used to replace dipropylene glycol. The prepared gel electrolyte cannot be completely removed from the template due to its excessive viscosity. It can be seen that in the present invention, dipropylene glycol has the function of adjusting the viscosity and fluidity of the gel electrolyte, and at the same time has a certain plasticizing effect on the gel electrolyte, thereby improving the flexibility of the gel electrolyte. The experimental results of Comparative Example 3 show that dipropylene glycol plays a vital role in the gel electrolyte formula system and cannot be simply replaced.

[0047] The gel electrolyte in Comparative Example 4 is prepared by replacing zinc trifluoromethanesulfonate with zinc methanesulfonate. It can be seen from the data test results that compared with Example 1, the conductivity and cycle time of Comparative Example 4 are significantly reduced. This may be because zinc trifluoromethanesulfonate has a fluorinated group, which can provide better electrochemical performance, especially in inhibiting the growth of zinc dendrites. Therefore, zinc trifluoromethanesulfonate cannot be simply replaced in the gel electrolyte system.

[0048] The difference between Comparative Example 5 and Example 4 is that commercially available zinc oxide nanoparticles (particle size <100nm) are used to replace the modified porous zinc oxide nanorods. From the test data, it can be seen (compared with Example 1) that the zinc oxide nanoparticles have limited performance improvement on the gel electrolyte. This may be because although the zinc oxide nanoparticles have a large specific surface area, electrons need to pass through more interfaces when transmitting between particles, which slows down the electron transmission rate and increases the possibility of electron recombination. At the same time, the nanoparticles may agglomerate, and the gaps between the particles are small, which is not conducive to electron transmission. The modified porous zinc oxide nanorods provided by the present invention are one-dimensional nanostructures, with fewer contact interfaces during electron transmission, avoiding the recombination of electrons with other ions, allowing electrons to be transmitted at a higher speed, and thus having better electron transmission performance.

[0049] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A gel electrolyte, characterized in that: The invention comprises the following components: a water-soluble monomer, water, an electrolyte salt, a first electrolyte additive, a crosslinking agent and an initiator; The first electrolyte additive includes dipropylene glycol and zinc trifluoromethanesulfonate.

2. The gel electrolyte according to claim 1, characterized in that The mass ratio of the dipropylene glycol, zinc trifluoromethanesulfonate and water is (1-3): (6-8):

10.

3. The gel electrolyte according to claim 1, characterized in that The gel electrolyte further includes a second electrolyte additive including zinc acetate.

4. The gel electrolyte according to claim 1, characterized in that The water-soluble monomer is an acrylamide monomer.

5. The gel electrolyte according to claim 1, characterized in that: The electrolyte salt is at least one of potassium hydroxide, sodium hydroxide and lithium hydroxide.

6. The gel electrolyte according to claim 1, characterized in that: The cross-linking agent is at least one of methylenebisacrylamide, N-hydroxymethylacrylamide, and acrylamide-PEG-hydroxyl; the initiator is at least one of potassium persulfate, ammonium persulfate, azobisisobutyronitrile, and azobisisoheptylnitrile.

7. The method for preparing a gel electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: adding the first electrolyte additive to the water in proportion, and performing a first stirring to obtain a first mixed solution; S2: adding the water-soluble monomer to the first mixed solution in proportion, stirring for a second time, continuing to add the crosslinking agent and the initiator, stirring for a third time, and obtaining a gel precursor solution; S3: injecting the gel precursor solution into the template, drying it under certain conditions, and then immersing the template containing the gel into an electrolyte salt solution, soaking it, and then taking the gel out of the template to obtain a gel electrolyte.

8. The method for preparing the gel electrolyte according to claim 7, characterized in that: In step S2, the mass concentration of the water-soluble monomer in the mixed solution is 0.25 g / mL to 0.3 g / mL.

9. The method for preparing a gel electrolyte according to claim 7, characterized in that: The electrolyte salt solution in step S3 contains a second electrolyte additive.

10. A zinc-air battery, characterized in that: The invention comprises the gel electrolyte according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • All-solid-state zinc air battery and gel electrolyte thereof

    CN108539330A

  • Organogel electrolyte, extremely low temperature zinc-air battery prepared from organogel electrolyte and preparation method of extremely low temperature zinc-air battery

    CN114725583A